The “Othering” of Men in Early Childhood Education: Applying Covey’s Seven Habits (Journal of School Administration Research and Development, 2016)
How do early childhood educators, parents, and administrators really feel about men working with young children? Should men work as teachers of young children from birth through 8 years of age? Is this women’s work? Does explicitly and implicitly excluding men from the early childhood education workforce benefit the early childhood community’s commitment to diversity? Young children should have a diverse range of experiences including learning from men in their early childhood education settings (Bullough, 2015). In order to effectively recruit and retain more men into the early childhood education profession, early childhood education staff, parents, and administrators have to address their overt and covert “othering” biases toward men working in early childhood education environments.